Market Segmentation Based On Push And Pull Factors Among Local Scuba Divers On Dive Destination - Saad, Mohd Fairus (2024)
Tourism malaysia reported that 76.8% of the respondents chose islands and beaches as the main attractions to visit malaysia, and one of the activities involved is scuba diving. Tourists prefer the coastal area in malaysia because of the pristine marine environment and long-stretched beaches, which attract both divers and non-divers. Scuba diving has shown a notable surge in popularity as a recreational pursuit within the malaysian context. Tourism malaysia and malaysia scuba diving association highlighted scuba diving as one of the essential activities in promoting tourism destinations in malaysia, and they advocate for the scuba dive operators to actively promote their products and services to the respective market segments. Nonetheless, the absence of significant statistical data challenges the scuba diving operators to strategize their marketing initiatives effectively. Thus, the main aim of this study is to identify the most important segmentation of demographic variables and motivations among scuba divers that influences their selection of diving destinations. The researcher adopted the quantitative method by using an online survey of scuba divers who had visited diving destinations in malaysia. The online survey was distributed via social media and the scuba divers’ association. The usable responses were 321, and the data were coded and analysed using spss software. This study implemented four analysis methods: reliability test, descriptive analysis, factor analysis, and analysis of variance (anova). Three (3) clusters emerged from the analysis: pro-divers,